2014
DOI: 10.3906/bot-1308-9
|View full text |Cite
|
Sign up to set email alerts
|

Root architecture adaptation of Pistacia atlantica subsp. atlantica according to an increasing climatic and edaphic gradient: case of a north–south transect in Algeria

Abstract: Roots are hidden by soil, making their excavation and measurement of their size very laborious (Gregory, 2006) and difficult to analyze (Rood et al., 2011). However, the study of their spatial distributions allows the discovery of their main sources of water and minerals (Lynch, 1995). Given the quantitative and qualitative heterogeneity in Abstract: Despite xeric conditions, Pistacia atlantica Desf. subsp. atlantica (Atlas pistachio) succeeds in developing impressive dendrometric dimensions (25-m high, 2-m tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…TAHERI ABKENAR et al [2013] studies also did not indicate significant differences among samples soil texture and saturation percentage in Khojir wild pistachio national park. LIMANE et al [2014] research confirmed large difference in soil texture of wild pistachio forest in Algeria.…”
Section: Discussionsupporting
confidence: 57%
“…TAHERI ABKENAR et al [2013] studies also did not indicate significant differences among samples soil texture and saturation percentage in Khojir wild pistachio national park. LIMANE et al [2014] research confirmed large difference in soil texture of wild pistachio forest in Algeria.…”
Section: Discussionsupporting
confidence: 57%
“…), located along the north-south transect were the same as those used in previous studies (Fig. 1, Limane et al 2014;Limane 2018).…”
Section: Selection Of Atlas Pistachio Populationsmentioning
confidence: 99%
“…can serve as an interesting model. Indeed, several publications have reported the high adaptability of Atlas pistachio to increasing aridity (from semi-arid to hyperarid ecoclimatic conditions) by leaf morphological and histological (Belhadj et al 2007;Belhadj et al 2008), root architecture (Limane et al 2014;Limane 2018), and leaf biochemical traits (Hadj Aissa 2004;Ait Saïd et al 2011). However, publications concerning its mycorrhizal status are scarce (Limane et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sampling was carried out randomly in dayate Aiat, Timzerth region, wilaya of Laghouat (Algeria). Bioclimatically, the study area is located in the arid zone, with a dry season of 11 months per year (Limane et al, 2014).The samples were placed in paper bags and stored in a cooler and then refrigerated until they were used in the laboratory. The identification of the plant was carried out by Professor Smail-Saadoun Noria, Director of the Natural Resources Laboratory (LRN), University Mouloud Maameri, Tizi-Ouzou (Algeria).The harvested leaves were dried in the shade at room temperature, lying on the laboratory bench for 10 days.…”
Section: Plant Materialsmentioning
confidence: 99%